2010
DOI: 10.3168/jds.2009-2731
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of psyllium in milk replacer for neonatal calves. 1. Effects on growth, digesta viscosity, rate of passage, nutrient digestibilities, and metabolites in blood

Abstract: Based on research in other species, inclusion of psyllium in milk replacer might improve nutrient utilization and gastrointestinal function in neonatal calves. Male Holstein calves were fed a milk replacer (22% crude protein, 20% fat) either without or with psyllium (1.1% of dry matter) from 2 d through 28 d of age. Milk replacer was reconstituted to 12.5% dry matter (DM) and fed at 12% of calf body weight (BW), adjusted weekly. Water was offered ad libitum but no starter was fed. Three calves per treatment we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Viscosity of fecal samples used for the determination of diet digestibility was evaluated according to an adaptation of the methodology of Cannon et al (2010) . Samples of 100 g of fresh feces were diluted in 120 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…Viscosity of fecal samples used for the determination of diet digestibility was evaluated according to an adaptation of the methodology of Cannon et al (2010) . Samples of 100 g of fresh feces were diluted in 120 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…Previously we reported that addition of psyllium to milk replacer increased viscosity of digesta in the abomasum and colon, decreased DM content of colonic digesta and feces, and decreased the passage rate of digesta in the total digestive tract of healthy neonatal calves (Cannon et al, 2010). As part of that study, the objective of the research reported here was to determine the effects of inclusion of psyllium in milk replacer on VFA concentrations and microbial populations throughout the GIT, as well as on weight, length, and density of GIT tissues in neonatal dairy calves.…”
Section: Introductionmentioning
confidence: 90%
“…All procedures were approved by the University of Illinois Institutional Animal Care and Use Committee (protocol number 04083). Details of selection of calves, general husbandry, and dietary management were presented previously (Cannon et al, 2010). Briefly, the study was conducted with 2 blocks of 12 and 22 male calves purchased from a local commercial dairy at less than 36 h of age.…”
Section: Animals and Feedingmentioning
confidence: 99%
“…Digestion rates of structural carbohydrates are often faster for feed based on legume than grasses. The higher rate of passage may, however, decrease the digestibility of some nutrients (Vieira et al, 2008;Cannon et al, 2010) and therefore affect performance. Differences between feeds, especially a physical dissimilarity regarding fibrous contents, determine alterations in feeding behavior, with a lower total intake time and an animal resting for longer as the amount of fiber decreases.…”
Section: Introductionmentioning
confidence: 99%